WEED CONTROL IN SUGARCANE (SACCHARUM OFFICINARUM L) WITH ASULAM AND ACTRIL DS. - FADAYOMI , OMOSUYI; ABAYOMI, Y. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Field studies were conducted at Ilorin between 1986 and 1987 10 evaluate the efficacy Of different concentrations and times of application of asulam (methyl (4-aminophenyl) sulfonyl) - carbamate), alone and in combination with Actril DS (a formulated mixture of ioxynil (4-hydroxy-3, 5-diiodobenzonitrite) and 2, 4-D (2, 4-(dichlorophenoxy) acetic acid)). for weed control in plant and first ratoon crops of sugarcane. Whether applied alone or in combination Actril DS, the rate of application of asulam did not significantly affect the level of weed control in both plant and ratoon crops. The mixture of asulam with Actril DS was, however more effective than asulam alone in the plant crop. Increasing asulam concentration beyond 3.5kg/ha resulted in slight reductions in cane yield in the plant crop, whereas yields increased with increasing concentration of asulam used in the ratoon crop. Cane yields in both the plant and ratoon crops decreased with an increase in the concentration of asulam combined with Actril DS. The time of application of the herbicides did not influence their weed control effectiveness in both the plant and ratoon crops. The herbicides were, however, more phytotoxic to the crop when applied 10 than when applied at either 6 or 3 weeks after planting in the plant crop. There was no difference in the level or phytotoxicity in the ratoon crop.